Epoxides related to dioncoquinone B: Synthesis, activity against multiple myeloma cells, and search for the target protein. Issue 38 (20th September 2018) - Cheng, Xia; Zhang, Guoliang; Seupel, Raina; Feineis, Doris; Brünnert, Daniela; Chatterjee, Manik; Schlosser, Andreas; Bringmann, Gerhard
Abstract: Epoxide 2b is an analog of the synthetic intermediate 2a en route to the polyketide-derived antitumoral naphthoquinone dioncoquinone B (1 ), isolated from cell cultures of the tropical liana Triphyophyllum peltatum (Dioncophyllaceae). Compound 2b was found to induce strong apoptosis in multiple myeloma cells at a concentration (EC50  = 3.5 μM), distinctly lower than that of 1 and any related analog, without exerting significant toxicity against normal blood cells. Preliminary studies showed that 2b follows different SAR rules as compared to the naphthoquinones. Among the series of synthesized epoxides, 2b was the most active one and was thus, after biotinylation, subjected to mass spectrometry-based affinity capture experiments aiming at the identification of target proteins. The MS data revealed 2b to address proteins that are associated with stress regulation processes which are critical for multiple myeloma cell survival. Graphical abstract: Image 1